Comparison of Clinical Cure Rates of Doxycycline and Levofloxacin in the Treatment of Acute Exacerbations of Chronic Obstructive Pulmonary Disease - Aslam, Amina; Asghar, Javed; Bashir, Abida; Akram, Sufyan; Jamil, Muhammad Irfan (Indus Journal of Bioscience Research, 2025)
Background: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are a major cause of morbidity and health-care utilisation. Comparative evidence for commonly used oral antibiotics in ambulatory settings remains limited. This study assessed the early clinical efficacy of doxycycline versus levofloxacin in outpatient AECOPD. Methods: This randomized controlled trial was conducted in the Pulmonology Department of Lahore General Hospital, Lahore, over a five-month period (January–May 2025) after obtaining Institutional Review Board approval (2025/ERC/20) and completing trial registration (NCT06915688). Adults aged 40–75 years with spirometry-confirmed COPD and an acute exacerbation were enrolled and randomly assigned to receive oral doxycycline 100 mg twice daily or levofloxacin 500 mg once daily for five days. Clinical cure, requiring fulfilment of at least four of six predefined criteria, was evaluated two days after treatment. Baseline and follow-up clinical and laboratory parameters were analysed using appropriate statistical tests. Results: A total of 131 participants completed follow-up (62 doxycycline, 69 levofloxacin). Overall clinical cure occurred in 85.5% of the levofloxacin group versus 67.7% of the doxycycline group (χ²=5.837, p=0.016). Restoration of oxygen saturation to 88–92% was significantly more frequent with levofloxacin (98.6% vs 87.1%; p=0.010), and follow-up SpO₂ was modestly higher (89.94±1.30% vs 89.42±1.27%; p=0.022). Reductions in temperature, respiratory rate, leukocytosis, and CRP were comparable between groups. Subgroup analyses showed greater benefit of levofloxacin in older adults, patients with COPD duration >5 years, and those with diabetes or hypertension. Conclusion: Levofloxacin demonstrated superior early clinical cure compared with doxycycline in ambulatory AECOPD, particularly in higher-risk phenotypes. These results support selective use of levofloxacin while balancing antimicrobial stewardship considerations.